Model of Consumer Decision Making: An Empirical Study at Credit Card Customer In Jakarta - Limakrisna, Nandan (International Review of Management and Marketing, 2018)
There is an increasing development of credit card products within the banking industry. This rapid pace of development has sparked fierce competition in the race to acquire shares in this business market. The methods used for this research are description and explanatory survey. This paper tests the hypothesis that sales competency and brand image are associated with consumer decision making by using the method analysis of multiple regression or path analysis. Information was collected from 100 credit card customers at Airport Executive Lounge in Terminal 3 Jakarta to support this hypothesis. This suggests that sales competence and brand image should be rationalized to increase customer decision making in choosing a credit card, but sales competence seems to be more dominant. The contribution this research can make to bank sales competence is very important in order for customers to be able to select a credit card, aside from making a selection based on credit card brand image only, because credit card sales competence can give clear information to customers about credit card products. Keywords: Sales Competence, Brand Image, Customer Decision JEL Classifications: M30, M31